EDUCATIONAL ENVIRONMENT OF PEDAGOGICAL UNIVERSITIES IN THE SYSTEM OF FORMING ACADEMIC INTEGRITY OF HIGHER EDUCATION STUDENTS - Коваленко, Катерина (SWorldJournal, 2025)
The article examines the educational environment of pedagogical universities as an important component of the formation of academic integrity of higher education applicants. The scientific and pedagogical literature was analyzed, which allowed us to deter